2020
DOI: 10.7554/elife.51461
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic post-translational modification profiling of Mycobacterium tuberculosis-infected primary macrophages

Abstract: Macrophages are highly plastic cells with critical roles in immunity, cancer, and tissue homeostasis, but how these distinct cellular fates are triggered by environmental cues is poorly understood. To uncover how primary murine macrophages respond to bacterial pathogens, we globally assessed changes in post-translational modifications of proteins during infection with Mycobacterium tuberculosis, a notorious intracellular pathogen. We identified hundreds of dynamically regulated phosphorylation and ubiquitylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 106 publications
2
49
0
Order By: Relevance
“…Glycosylation, phosphorylation, lipidation, formylation, pupylation, acetylation, and methylation have been identified in M. tuberculosis [88,89]. Several studies have elucidated extensive networks of reversible (S/T/Y) protein phosphorylation in mycobacteria [90][91][92][93], during mycobacterial infection [91,94], and the identification of irreversible protein N-terminal acetylation as an abundant PTM in mycobacteria associated with virulence and survival [17,95].…”
Section: Targeted and Comprehensive Proteomic Approaches Define The Mmentioning
confidence: 99%
“…Glycosylation, phosphorylation, lipidation, formylation, pupylation, acetylation, and methylation have been identified in M. tuberculosis [88,89]. Several studies have elucidated extensive networks of reversible (S/T/Y) protein phosphorylation in mycobacteria [90][91][92][93], during mycobacterial infection [91,94], and the identification of irreversible protein N-terminal acetylation as an abundant PTM in mycobacteria associated with virulence and survival [17,95].…”
Section: Targeted and Comprehensive Proteomic Approaches Define The Mmentioning
confidence: 99%
“…were analyzed using liquid chromatography and mass spectroscopy, as previously described (31). Mass spectrometry data was assigned to E. coli sequences and MS1…”
Section: Liquid Chromatography Mass Spectroscopy and Label-free Quanmentioning
confidence: 99%
“…To understand how splicing regulatory proteins shape global innate immune gene expression, we first needed to identify factors most likely to play a privileged role in the macrophage innate immune response. Two recent publications identified a number of splicing factors that were differentially phosphorylated during bacterial infection (specifically during infection with the intracellular bacterial pathogen Mycobacterium tuberculosis) in a RAW 264.7 macrophage cell line [32] or in primary mouse macrophages [33]. We manually annotated these lists and prioritized a set of SRSF and hnRNPs for transcriptomics analysis.…”
Section: Salmonella-infected Macrophagesmentioning
confidence: 99%
“…SR proteins often work cooperatively and antagonistically with proteins in the heterogenous nuclear ribonucleoprotein (hnRNP) family, which also bind to conserved sequences in exons and introns to influence splicing decisions. We became interested in a role for SR and hnRNP proteins in regulating macrophage gene expression after several global phosphoproteomics studies revealed that proteins involved in mRNA processing are among the most differentially phosphorylated proteins in macrophages following infection with a bacterial [27,28] or fungal pathogen [29], despite showing no significant change in protein abundance. These data led us to speculate that splicing regulatory proteins are functionalized following pathogen sensing.…”
Section: Introductionmentioning
confidence: 99%